Pembelajaran Siswa Sekolah Dasar dengan Bumbu Dapur Sebagai Obat Tradisional yang Manjur - dwiatmaka, yohanes; Wulandari, Erna Tri; Setiawati, Agustina; Hartinni, Yustina Sri; Permatasari, Olga Sancaya Dyah; Widiyanto, Yohanes Baptista Cahya (Universitas Katolik Soegijapranata, 2024)
This community service target were class VI students at Kanisius Duwet Elementary School (SDK Duwet), Sleman, Yogyakarta. The team consists of lecturers from the Department of Pharmacy and Psychology at Sanata Dharma University (SDU), assisted by several students. Implementation of Phase-1 for the introduction of spices and herbal plants: garlic, shallots, ginger, turmeric, and galangal. Phase-1 was carried out with a direct visit to the Medicinal Plant Garden Laboratory, Faculty of Pharmacy, SDU. Stage-2 activities were carried out at SDK Duwet, carried out in the form of practical training in making and using several traditional medicines (TM) from kitchen spices that had been introduced in stage-1. Student understanding was measured through pretest and posttest. The result of the phase-1 pretest was very good (mean 90.53). Only a few students (23.68%) did not know galangal and turmeric. In phase-2 the mean pretest score was 60.53, lower than in phase-1. This showed that students knew the names of spices, but did not know their benefits as TM. Phase-2 posttest results with a mean of 89.71. According to the t-test between posttest and pretest in phase-2, students' understanding significantly increased by 148% (P0.01). This service program was successful in improving students' understanding and skills. The activity was closed with a group presentation. During the group presentation, students were enthusiastic in their delivery and stated that they were very impressed and amazed by this new knowledge about traditional medicines.